DETERMINAN PILIHAN KARIR PADA MAHASISWA AKUNTANSI (Studi Empiris pada Mahasiswa Akuntansi S1 Universitas Diponegoro) - Widiatami, Anna Kania; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2013)
This research is aimed to learn the influence of factors: level of students, salary, professional training, social values, professional confession, and job enviroment toward to the choice of carrirer of accounting students with gender as a control variable. The research data is found by purposive sampling and convience sampling technics for undergraduate accounting students in Diponegoro University. There are 571 total population of students, with Slovin formula obtained 85 respondents consisting of 40 respondens of junior student and 45 respondens of senior student. To test some hypothesis in this research, researcher use Multinomial Logit method as data analyst tool.The result of the research shows that factors: professional training, social values, professional confession, and job enviroment influence the choice of carrier of accounting students. While level of students and salary factors not influence the choice of carrier of accounting students.